Bidirectional Boost/Buck Quadratic Converter for Distributed Generation Systems with Electrochemical Storage Systems - Foito, Daniel José Medronho (2017)
Trabalho apresentado no 5th IEEE International Conference on Renewable Energy Research and Applications, 20-23 de novembro 2016, Birmingham, Reino Unido